Hubungan Pemberian Makanan Tambahan (Pmt) Dengan Kejadian Stunting Pada Anak Usia 24¬-36 Bulan Diwilayah Kerja Puskesmas Pajarakan - Syarifatul Jannah; Iis Hanifah; Muthmainnah Zakiyyah (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
This study analyzes the relationship between the provision of additional food (PMT) and the incidence of stunting in toddlers aged 24–36 months in the Pajarakan Health Center working area. Using a quantitative approach with a cross-sectional design, the sample consisted of 73 toddlers selected randomly. Data were collected through questionnaires and height measurements, then analyzed using the Chi-Square test. The results showed a significant relationship between the provision of PMT and the incidence of stunting (p-value 0.001). This finding is expected to increase mothers' awareness in paying attention to parenting patterns and child nutrition.